Effects of bioaugmentation by isolated Achromobacter xylosoxidans BP1 on PAHs degradation and microbial community in contaminated soil. (15th May 2023) - Zhang, Ben; Xu, Wei; Ma, Yichi; Gao, Xiaolong; Ming, Huyang; Jia, Jianli
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are a group of organic pollutants ubiquitous and persistent in soil. In order to provide a viable solution for bioremediation of PAHs-contaminated soil, a strain of Achromobacter xylosoxidans BP1 with superior PAHs degradation ability was isolated from contaminated soil at a coal chemical site in northern China. The degradation of phenanthrene (PHE) and benzo[a]pyrene (BaP) by strain BP1 was investigated in three different liquid phase cultures, and the removal rates of PHE and BaP by strain BP1 were 98.47% and 29.86% after 7 days under the conditions of PHE and BaP as the only carbon source, respectively. In the medium with the coexistence of PHE and BaP, the removal rates of BP1 were 89.44% and 9.42% after 7 days, respectively. Then, strain BP1 was investigated for its feasibility in remediating PAH-contaminated soil. Among the four PAHs-contaminated soils treated differently, the treatment inoculated with BP1 exhibited higher removal rates of PHE and BaP (p < 0.05), especially the CS-BP1 treatment (inoculation of BP1 into unsterilized PAHs-contaminated soil) showed 67.72%, 13.48% removal of PHE and BaP, respectively, over 49 days of incubation. Bioaugmentation also significantly increased the activity of dehydrogenase and catalase in the soil (p＜0.05). Furthermore, the effect of bioaugmentation on the removal of PAHs was investigated by measuring the activity of dehydrogenase (DH) and catalase (CAT) during incubation. Among them, the DH and CAT activities of CS-BP1 and SCS-BP1 (inoculation of BP1 into sterilized PAHs-contaminated soil) treatments inoculated with strain BP1 were significantly higher than those of treatments without BP1 addition during incubation (p < 0.01). The structure of the microbial community varied among treatments, but the Proteobacteria phylum showed the highest relative abundance in all treatments of the bioremediation process, and most of the bacteria with higher relative abundance at the genus level also belonged to the Proteobacteria phylum. Prediction of microbial functions in soil by FAPROTAX analysis showed that bioaugmentation enhanced microbial functions associated with the degradation of PAHs. These results demonstrate the effectiveness of Achromobacter xylosoxidans BP1 as a PAH-contaminated soil degrader for the risk control of PAHs contamination. Graphical abstract: Image 1 Highlights: AcHromobacter xylosoxidans BP1 was isolated from a coal chemical cite. Strain BP1 showed good PHE degradation and cell growth in the liquid phase. Bioaugmentation showed to be effective for bioremediation of PHE and BaP. Inoculation of strain BP1 improved the complexity of the soil microbiomes network.